Combustion Quality Analysis of Bio-Briquettes from Mixture of Coconut Shell Waste and Coal with Tapioca Flour Adhesive - Dhias Cahya Hakika; Siti Jamilatun; Shafa Zahira; Riska Setyarini; Aster Rahayu; Remmo Sri Ardiansyah (Universitas Ahmad Dahlan, 2023)
Agroindustry residues can be utilized as a resource for alternative energy sources such as bio-briquettes. Using agro-industry residue is also a solution to reduce pollution caused by biomass waste in the environment. This article highlights the combustion quality analysis of biomass waste in the form of bio-briquettes with binding materials prepared from tapioca flour. The biomass used is a mixture of coconut shell charcoal and coal to improve the quality of the bio-briquettes. In this study, bio-briquettes were manufactured using a screw press system. The combustion quality of bio-briquettes with various percentage compositions (0:100, 25:75, 50:50, 75:25, 100:0) of coconut shell charcoal and coal was investigated, i.e., moisture content, ash content, combustion rate, and calorific value. Results show that the calorific value of most bio-briquettes produced in this study was higher than the standard calorific value according to SNI Standard No.1/6235/2000 (≥ 5,000 cal/gr). The optimum composition to produce bio-briquette with good quality based on the standard is 75:25 (coconut shell charcoal: coal), which had a moisture content of 7.6325%, ash content of 6.9697%, combustion rate of 0.1833 gr/min, and caloric value of 5833.78 cal/gr.